2019
DOI: 10.1038/s41388-019-0925-0
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory networks in mechanotransduction reveal key genes in promoting cancer cell stemness and proliferation

Abstract: Tumor-repopulating cells (TRCs) are cancer stem cell (CSC)-like cells with highly tumorigenic and self-renewing abilities, which were selected from tumor cells in soft three-dimensional (3D) fibrin gels with unidentified mechanisms. Here we evaluated the transcriptome alteration during TRCs generation in 3D culture and revealed that a variety of molecules related with integrin/membrane and stemness were continuously altered by mechanical environment. Some key regulators such as MYC/STAT3/hsa-miR-199a-5p, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 55 publications
3
26
0
Order By: Relevance
“…Previous studies have shown that YAP expression is regulated by β-catenin at the transcriptional level of HCC [30,31]. In this study, free hGC33 and nanodrug surface-modified hGC33 inhibited Wnt3a-induced YAP activity, indicating that Yap/ TAZ released from β-catenin complex can also initiate classic Wnt signaling transduction [32,2]. These results indicate that typical Wnt and YAP cross talk through a variety of mechanisms.…”
Section: Discussionsupporting
confidence: 61%
“…Previous studies have shown that YAP expression is regulated by β-catenin at the transcriptional level of HCC [30,31]. In this study, free hGC33 and nanodrug surface-modified hGC33 inhibited Wnt3a-induced YAP activity, indicating that Yap/ TAZ released from β-catenin complex can also initiate classic Wnt signaling transduction [32,2]. These results indicate that typical Wnt and YAP cross talk through a variety of mechanisms.…”
Section: Discussionsupporting
confidence: 61%
“… 34‐38 Signal transducer and activator of transcription 3 plays key roles in multiple cancer‐related signaling pathways and is aberrantly expressed in various human cancers 39 . Activation of STAT3 is associated with cancer stem cell properties such as tumor seeding ability and drug resistance 40,41 . The small molecule napabucasin (BBI608) was identified as a STAT3 inhibitor that targets cancer stem cells 35 .…”
Section: Clinical Evaluation Of Small Molecule Inhibitors Targeting Dmentioning
confidence: 99%
“…Furthermore, only four to six DMGs of CSC marker genes had methylation changes in upstream regulatory region, confirming methylation changes of these genes were more likely to occur in the gene body region. The expression levels of mechanotransduction genes that were changed significantly from HeLa 2D to HeLa TRCs in 3day samples in the previous project (Huang et al, 2019) here were also changed significantly in non-CG methylation (Supplementary Figure S4). The enrichment of DMRs contained in stemness marker genes in each chromatin state region was further analyzed (Figure 5E).…”
Section: Methylation Pattern Analysis Of Csc Marker Genes In Dmgsmentioning
confidence: 54%
“…Thus, the process of TRC selection/transformation is a very good model to study the origin, regulation, and inner mechanisms of CSCs. Our previous work has provided insights into the mechanisms of TRC selection through transcriptome analysis (Huang et al, 2019). Currently, it is believed that DNA methylation plays an important role in maintaining the proliferation and differentiation of progenitor cells, as well as the stemness of CSCs (Sen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%